2008
DOI: 10.1517/17460441.3.5.565
|View full text |Cite
|
Sign up to set email alerts
|

New tuberculosis drug development: targeting the shikimate pathway

Abstract: Shikimate pathway enzymes, especially shikimate kinase, may offer attractive targets for new TB drug and vaccine development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 114 publications
(140 reference statements)
0
8
0
Order By: Relevance
“…Chorismic acid, which is synthesized through the shikimic acid pathway, is the precursor of aromatic amino acids and other metabolites, including folates, ubiquinones, mycobactins, menaquinones, and napthoquinones 3 . Genomic studies have shown that this biosynthetic route is essential in bacteria, fungi, algae, higher plants, and some parasites, such as the human malaria-causing parasite Plasmodium falciparum 4 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Chorismic acid, which is synthesized through the shikimic acid pathway, is the precursor of aromatic amino acids and other metabolites, including folates, ubiquinones, mycobactins, menaquinones, and napthoquinones 3 . Genomic studies have shown that this biosynthetic route is essential in bacteria, fungi, algae, higher plants, and some parasites, such as the human malaria-causing parasite Plasmodium falciparum 4 6 .…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme is considered an excellent target for developing novel anti-tuberculosis agents as the pathway in which it is involved only takes place in microbes and some plants but is absent in mammals [ 11 ]. The shikimate pathway involves seven enzymatic steps in the biosynthesis of chorismate end product, which in turn serves as the precursor for the synthesis of the aromatic amino acids, folates, uniquinones, mycobactins, menaquinones and napthoquinones [ 12 ]. The importance of this pathway has been proven in culture using mutants whose growth is completely inhibited without the provision of aromatic supplements [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This route, that combines glucose and pentose phosphate metabolism, involves seven reactions that convert erytrose-4-phosphate and phosphoenolpyruvate to chorismate, which is the precursor for the synthesis of important metabolites such as aromatic amino acids, ubiquinone and folate [8]. The shikimate pathway is present in plants, fungi, apicomplexan parasites and bacteria, but is absent in humans, a characteristic that makes its enzymes excellent targets for drug discovery [8,9,10].…”
Section: Introductionmentioning
confidence: 99%